Development of a Scheduled Waste Inventory and Monitoring System (SWIMS) to Improve Operational Efficiency and Inventory Accuracy in the Homecare Manufacturing Sector, Petaling Jaya - Mohammad Izzudin Basri,; Amir Haziq Abdul Razak,; Asmidi Farhan Mashan, (Progress in Engineering Application and Technology, 2026)
Scheduled Waste management in Malaysia is a strict legal requirement under the Environmental Quality Act 1974. However, many factories still use manual logbooks, which cause data gaps between physical stock and the official eSWIS digital system. This study developed the Scheduled Waste Inventory and Monitoring System (SWIMS) using low-code tools like Google Workspace to replace paper-based tracking. The objective was to automate mass balance calculations and reduce human errors that lead to fines or safety risks. The methodology followed a quantitative before-and-after design, comparing manual records against the digital system over an eight-week industrial pilot. Results showed that SWIMS significantly improved data accuracy and cut down administrative time compared to the manual baseline. The system effectively acted as a safeguard during high-production periods when manual mistakes usually peak. To improve this further, future work should focus on linking IoT digital scales to the database and enabling direct data syncing with the Department of Environment’s eSWIS platform. This research proves that simple digital tools can help EHS teams move from basic record-keeping to active risk management.